AKSENTUASI NILAI NORMATIF RASULULLAH: (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2022)
Fethullah Gulen is a well-known religious leader and Islamic preacher in Turkey. Gülen is well renowned for his